SOCIALIZATION OF COUNSELING AND INNOVATION IN THE DEVELOPMENT OF SLAM TEA PRODUCTS - Teguh Adiyas Putra; Nurhasanah Nurhasanah; Eka Ratnasari; Fika Nurul Hidayah (Jurnal Abdisci, 2024)
Counseling on bay leaf tea bag MSME products is expected so that the residents of Salam Hamlet can understand and understand the benefits of bay leaves for health, especially in overcoming hypertension. And can set an example to make similar herbal tea products that can be used as a product that can be sold by residents. The place where community service activities are carried out is Salam Hamlet, Sarewu Village, RW 03, Pancalang District, Kuningan Regency has high-quality knowledge and health degrees so that a healthy community and environment are created. Community service activities are in the form of counseling, tea making, and the design and packaging of bay leaf tea. The participants of this counseling activity were very enthusiastic and were conducive. Many people ask in terms of its use in the manufacturing process. However, the testers of bay leaf tea bags and bay leaf tea bags distributed to participants were very limited because there were obstacles in the manufacturing process, namely in the drying because it always rained every day, so it hindered the drying process because we dried with sunlight (not using an oven) due to the limitations of the tools at the post. In the next development and innovation process, we have also made logo and packaging designs for bay leaf tea.